INTERCULTURAL COMMUNICATIVE COMPETENCE OF STUDENTS FROM DIFFERENT CULTURES IN EFL CLASSROOM INTERACTION IN HIGHER INSTITUTION - Sukardi Weda; Fathu Rahman; Haryanto Atmowardoyo; Iskandar Abdul Samad; Siti Sarah Fitriani; Mawardin M. Said; Andi Elsa Fadhilah Sakti (Institut Agama Islam Negeri (IAIN) Bone, 2022)
The authors address the study on intercultural communicative competence (ICC) of EFL students from different culture at higher education in the classroom setting. ICC is the most interesting and important topic in every meeting among people from different ethnic groups. López-Rocha (2016) mentions that intercultural communicative competence (ICC) needs to be incorporated in the language curriculum if educators hope to help students develop an appreciation for the language and culture studied, an awareness of their own culture, and the development of skills that will allow them to be competent, adaptable, and communicators. This present study therefore aims at exploring students’ perceptions on the practice of intercultural communication competence in EFL classroom at English Department, Faculty of Languages and Literature State University of Makassar, Indonesia in 2019/2020 academic year. A questionnaire was distributed and responded by fifty four undergraduate students. The data obtained from respondents were analyzed using descriptive statistics illustrating mean, standard deviation (SD), sum, and percentage of students’ perceptions on the questionnaire dealing with ICC practices in EFL classroom. The findings reveal that the students enjoy interacting with other students from different cultures. Other evidences from the study are: 1) they find it easy to talk to students from different cultures, 2) they like to be with students from different cultures, 3) they are open-minded to students from different cultures, 4) they respect the ways students from different cultures behave, 5) They try to get as much information as they can when interacting with students from different cultures, 6) they never think their culture is better than other cultures, 7) they often give positive responses to students from other cultures when maintaining interaction, and 8) they have a feeling of enjoyment towards diversity in their classroom interaction. The implication of the study is that the inclusion of ICC in the curriculum at higher education is a must.